Answer: (2, 1)
======================================================
Step-by-step explanation:
Let's add the equations straight down
- The x terms add up to 2x+x = 3x
- The y terms add to -y+y = 0y = 0, so the y terms go away
- The right hand sides add to 3+3 = 6
After those three things happen, we're left with 3x = 6 which solves to x = 2 after dividing both sides by 3.
Now let's use this x value to find y
2x-y = 3
2(2)-y = 3
4-y = 3
-y = 3-4
-y = -1
y = 1
Or we could use the other equation
x+y = 3
2+y = 3
y = 3-2
y = 1
which gets us there in fewer steps.
So that's how we get to the final answer of (x,y) = (2,1)
The graph is shown below.